PENGARUH PENERAPAN METODE ACTIVE LEARNING TIPE CARD SORT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS X MA AN-NUR BULULAWANG - Bunga Vanda Meillynia; Ika Ratih Sulistiani; Muhammad Sulistiono (VICRATINA, 2022)
This research was conducted to determine the effect of the application of the card sort type of active learning method on the learning outcomes of aqidah morals in the chapters of mandatory nature for Allah, impossible for Allah, and jaiz for Allah. The design of this study used a quasi-experimental quantitative research. The data collection technique used student learning outcomes, student perception questionnaires and documentation. Then this data analysis technique uses a paired two-sample t-test and processing this data using the SPSS Version 23.0 computer program with a significance level of 5%. The result data obtained from the post-test scores in the Experimental class obtained an average score of 81.08, while the Control class obtained an average score of 73.26. and the results of the t-test analysis in this study obtained a value of 0.000 this indicates that the value of sig(2-tailed) <0.05, while the results obtained by distributing questionnaires to 23 students, from a scale of 100% with a presentation of 69.6% students choose "strongly agree" that the card sort type of active learning method is very influential in improving student learning outcomes for that the card sort type of active learning method is one of the right methods in encouraging students to be more active in learning so that it can affect student learning outcomes.